DO INDONESIAN GOVERNMENT DEPLOY RELIABLE AMMUNITION FOR COVID-19 MASS TEST? A COMPARISON OF REAL-TIME PCR KITS - MARISSA, NELLY; SALMIATY; HANUM, SARI; FEBRIANSYAH, EVAN; RAMADHAN, NUR; YULIDAR; HADIFAH, ZAIN; PRANATA, AGUNG (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: This study aimed to compare the level of reliability of three commercial real-time PCR kits in determining clinical samples. Methods: A total of 40 swabs samples which were previously tested positive, were re-test using the BioCov-19 RT-PCR kit, Sansure coronavirus disease 19 (COVID-19) nucleic acid diagnostic kit, and Kogen PowerCheck with Thermocycler (Roche). The amplification procedure is carried out based on the manual for each kit. Results: Sansure COVID-19 nucleic acid diagnostic was able to detect 40 samples with positive severe acute respiratory syndrome coronavirus 2 (SARS-COV-2) results detected in both genes, while the PowerChek™ 2019-nCoV real-time PCR kit able to detect 35 samples showed that SARS-COV-II was detected in both genes, and the BioCoV-19 RT-PCR Kit brand kit able to detect 34 samples showed positive SARS-COV-2 results in both genes. Conclusion: The three commercial kits show great ability detection, so that they can be used to detect the presence of SARS-COV-II in clinical samples, and also in mass screening.